Effects of climate change on Platanus flowering in Western Mediterranean cities: current trends and future projections - Picornell Rodríguez, Antonio; Maya-Manzano, José M.; Fernández-Ramos, Marta; Hidalgo-Barquero, Juan J.; Pecero-Casimiro, Raúl; Ruiz-Mata, Rocío; De Gálvez-Montañez, Enrique; Trigo-Pérez, María del Mar; Recio-Criado, María Marta; Fernández-Rodríguez, Santiago (Elsevier, 2023)
Ornamental trees can reduce some of the negative impacts of urbanization on citizens but some species, such as Platanus spp., produce pollen with high allergenic potential. This can exacerbate the symptomatology in allergic patients, being a public health problem. Therefore, it would be relevant to determine the environmental conditions regulating the flowering onset of the Platanus species. The aims of this study were to use aerobiological records for modelling the thermal requirements of Platanus flowering and to make future projections based on the effects that climate change could have on it under several possible future scenarios. This study was conducted in Badajoz and Malaga, two Western Mediterranean cities with different climate conditions. In the first step, several main pollen season definitions were applied to the aerobiological data and their onset dates were compared with in situ phenological observations. The main pollen season definition that best fitted the Platanus flowering onset was based on the 4th derivative of a logistic function. This definition was used as a proxy to model the thermal requirements of the Platanus flowering onset by applying the PhenoFlex statistical framework. The errors obtained by this model during the external validation were 3.2 days on average, so it was fed with future temperature estimations to determine possible future trends. According to the different models, the flowering onset of Platanus in Badajoz will show heterogeneous responses in the short and medium term due to different balances in the chilling-forcing compensation, while it will clearly delay in Malaga due to a significant delay in the chilling requirement fulfilment. This may increase the chances of cross-reactivity episodes with other pollen types in the future, increasing its impact on public health.
Keywords: Botánica; Fisiología vegetal; Cambios climáticos; Botany; Platanus spp.; Phenology; Climate change; Forecast